2004
DOI: 10.1371/journal.pbio.0020198
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection of Naturally Occurring and Genetically Reprogrammed Human Regulatory T-cells

Abstract: A T-cell subset, defined as CD4+CD25hi (regulatory T-cells [Treg cells]), was recently shown to suppress T-cell activation. We demonstrate that human Treg cells isolated from healthy donors express the HIV-coreceptor CCR5 and are highly susceptible to HIV infection and replication. Because Treg cells are present in very few numbers and are difficult to expand in vitro, we genetically modified conventional human T-cells to generate Treg cells in vitro by ectopic expression of FoxP3, a transcription factor assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
336
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(367 citation statements)
references
References 75 publications
25
336
3
2
Order By: Relevance
“…Importantly, our data demonstrate that when overexpressed, both Foxp3 isoforms are capable of converting conventional CD4 + CD25 -cells into Treg. These latter results confirm and extend the findings of three other studies in the human setting [13,15,16] and of several studies in mice [3,4,[17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, our data demonstrate that when overexpressed, both Foxp3 isoforms are capable of converting conventional CD4 + CD25 -cells into Treg. These latter results confirm and extend the findings of three other studies in the human setting [13,15,16] and of several studies in mice [3,4,[17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 91%
“…Currently, little is known about the cellular distribution and expression ratio of these human Foxp3 isoforms. Furthermore, conflicting reports appeared on the functional properties of human Foxp3 genes: while three studies reported conversion of conventional T cells into Treg after ectopic expression of Foxp3FL [13,15,16], another study failed to induce Treg after retroviral transduction of conventional T cells with either Foxp3FL or Foxp3DE2 [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, CCR4 is also crucial for homing of Th cells and Th2, mainly memory T cells, into inflamed skin (39). In fact, we found CD4 ϩ CD25 Ϫ T cells in the blood and lesions coexpressing CCR4 and CD45RO, a phenotype related to memory T cells (40).…”
Section: Discussionmentioning
confidence: 65%
“…Regulatory T cells (CD4 + CD25 + ) are a crucial component for the control of deleterious effects from excessive immune responses as seen in autoimmune disease or allergic insult [1,2]. Treg cells have been implicated in a number of pathologic processes including elevated levels in cancers [3][4][5] and infectious diseases [6][7][8][9], and reduced levels in autoimmune diseases [1,[10][11][12][13]. It is apparent that Treg cells are induced (or recruited and expanded) by most infections to modulate host immune responses to avoid overreactive immunity (Fig.…”
Section: Regulatory T Cells Play An Important Role In Self Immune Tolmentioning
confidence: 99%